Answer:
Julio travel <u>3 hours</u> by biking and <u>4 hours</u> by walking.
Step-by-step explanation:
Given:
Julio started biking to the park traveling 8 mph, after some time the bike got a flat so Julio walked the rest of the way, traveling 7 mph.
If the total trip to the park took 7 hours and it was 52 miles away.
Now, to find the time Julio travel at each speed.
The speed travelled by the bike = 8 mph.
The speed travelled by the walking = 7 mph.
Let the time Julio travel with bike be ![x.](https://tex.z-dn.net/?f=x.)
And the time Julio travel by walking be ![y.](https://tex.z-dn.net/?f=y.)
As, given Julio started biking to the park traveling, after some time the bike got a flat so Julio walked the rest of the way,
Thus, the total time taken:
![x+y=7](https://tex.z-dn.net/?f=x%2By%3D7)
![y=7-x\ \ \ .......(1)](https://tex.z-dn.net/?f=y%3D7-x%5C%20%5C%20%5C%20.......%281%29)
So, the distance travelled by bike:
Speed × time
![8\times x=8x](https://tex.z-dn.net/?f=8%5Ctimes%20x%3D8x)
And, the distance travelled by walking:
Speed × time
![7\times y=7y](https://tex.z-dn.net/?f=7%5Ctimes%20y%3D7y)
Now, the total distance travelled by Julio:
![8x+7y=52](https://tex.z-dn.net/?f=8x%2B7y%3D52)
Substituting the value of
from equation (1) we get:
![8x+7(7-x)=52](https://tex.z-dn.net/?f=8x%2B7%287-x%29%3D52)
![8x+49-7x=52\\\\x+49=52](https://tex.z-dn.net/?f=8x%2B49-7x%3D52%5C%5C%5C%5Cx%2B49%3D52)
<em>Subtracting both sides by 49 we get:</em>
![x=3.](https://tex.z-dn.net/?f=x%3D3.)
<em>The time Julio travelled with bike = 3 hours.</em>
Now, to get the time Julio travelled by walking by substituting the value of
:
![y=7-x\\\\y=7-3\\\\y=4\ hours.](https://tex.z-dn.net/?f=y%3D7-x%5C%5C%5C%5Cy%3D7-3%5C%5C%5C%5Cy%3D4%5C%20hours.)
<em>The time Julio travelled by walking = 4 hours.</em>
Therefore, Julio travel 3 hours by biking and 4 hours by walking.